2009
DOI: 10.1155/2009/904589
|View full text |Cite
|
Sign up to set email alerts
|

Detection of EBV Infection and Gene Expression in Oral Cancer from Patients in Taiwan by Microarray Analysis

Abstract: Epstein-Barr virus is known to cause nasopharyngeal carcinoma. Although oral cavity is located close to the nasal pharynx, the pathogenetic role of Epstein-Barr virus (EBV) in oral cancers is unclear. This molecular epidemiology study uses EBV genomic microarray (EBV-chip) to simultaneously detect the prevalent rate and viral gene expression patterns in 57 oral squamous cell carcinoma biopsies (OSCC) collected from patients in Taiwan. The majority of the specimens (82.5%) were EBV-positive that probably exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 56 publications
(64 reference statements)
1
29
0
2
Order By: Relevance
“…HSV nucleic acids have been found in lip cancer (39), antibody levels to HSV-1 and -2 are higher in oral cancer patients when compared with controls, and HSV seropositivity together with smoking has been associated with increased cancer risk (27). Epstein-Barr virus has also been implicated in oral cancer but the evidence thus far is controversial (40)(41)(42)(43)(44)(45).…”
Section: -Virus Infections • Human Papillomavirus Infectionsmentioning
confidence: 99%
“…HSV nucleic acids have been found in lip cancer (39), antibody levels to HSV-1 and -2 are higher in oral cancer patients when compared with controls, and HSV seropositivity together with smoking has been associated with increased cancer risk (27). Epstein-Barr virus has also been implicated in oral cancer but the evidence thus far is controversial (40)(41)(42)(43)(44)(45).…”
Section: -Virus Infections • Human Papillomavirus Infectionsmentioning
confidence: 99%
“…By using EBV chips, Yen et al 51 have demonstrated an increased sensitivity of EBV detection rate in oral cancer cells as compared with traditional molecular assays (from 15–77% to 82·5%).…”
Section: Pathological and Virological Techniques: Clinical Applicationsmentioning
confidence: 99%
“…As propriedades biológicas desses 2 tipos são também distintas, o EBV-1 é mais potente do que o EBV-2 na transformação e imortalização de linfócitos B infectados in vitro, mais ambos os tipos de EBV podem atuar como patógenos humanos 3,10 . Muitos estudos têm demonstrado que a expressão de genes virais latentes, especialmente os genes EBNAs e LMP-1 (proteína de membrana latente-1), tem sido intimamente associado com infecção latente que se correlaciona com a imortalização e carcinogênese 11 .…”
Section: Epstein-barr Vírusunclassified
“…O DNA do EBV tem sido isolado com frequência em células do carcinoma de nasofaringe, e está consistentemente associado ao seu desenvolvimento, sendo considerado como um dos seus fatores de risco 17 . Devido ao aumento na detecção de EBV em muitos cânceres, inúmeras pesquisas moleculares sobre o câncer oral, que usam principalmente PCR e métodos de hibridização in situ para detecção do DNA viral e transcrições de RNA, têm sido realizadas em todo o mundo 11 . Até hoje foram usadas várias técnicas em diferentes tipos de fontes de materiais são realizados para detectar o EBV em neoplasias, obtendo diferentes porcentagens de detecção, como demonstrado no quadro na página seguinte.…”
Section: Epstein-barr Vírusunclassified